2013
DOI: 10.3390/cancers5020372
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Epsilon and Genetic Networks in Osteosarcoma Metastasis

Abstract: Osteosarcoma (OS) is the most common primary malignant tumor of the bone, and pulmonary metastasis is the most frequent cause of OS mortality. The aim of this study was to discover and characterize genetic networks differentially expressed in metastatic OS. Expression profiling of OS tumors, and subsequent supervised network analysis, was performed to discover genetic networks differentially activated or organized in metastatic OS compared to localized OS. Broad trends among the profiles of metastatic tumors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Discs large MAGUK scaffold protein 2 (DLG2, also called PSD‐93) is a tumour suppressor that acts as a scaffold at cell‐cell junctions . It is found that the differentially expressed DLG2 can interact with PRKCε‐RASGRP3‐GNB2 network in osteosarcoma cell lines . In addition, the recurrent somatic mutation of DLG2 was also found in osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Discs large MAGUK scaffold protein 2 (DLG2, also called PSD‐93) is a tumour suppressor that acts as a scaffold at cell‐cell junctions . It is found that the differentially expressed DLG2 can interact with PRKCε‐RASGRP3‐GNB2 network in osteosarcoma cell lines . In addition, the recurrent somatic mutation of DLG2 was also found in osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, three differentially expressed mRNAs including up‐regulated Krüppel‐like factor 10 (Klf10) and down‐regulated paired box 8 (Pax8) and PR/SET domain 16 (Prdm16) were included in these processes. KLF10 (also called EGR‐alpha, EGRA, TIEG, and TIEG1) is a member of the Krüppel family of transcription factors and plays various roles in cell proliferation, differentiation, bone formation, and mineralization in human osteoblasts . It is indicated that deletion of KLF10 in osteoblasts leads to disorders of canonical and noncanonical Wnt signalling pathways during the course of osteoblasts differentiation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, in investigations of IGF-1R expression, increased expression of IGF-1R was closely associated with malignant metastasis and prognosis of OS, and high expression of IGF-1R in OS patients was associated with poorer prognosis [ 97 ]. In addition, inhibition of growth hormone release in mice by growth shift analogs or growth hormone-releasing hormone antagonists reduces serum IGF-1 levels and inhibits tumor growth, possibly because these compounds reduce IGF-I stimulation and directly affect cell growth [ 98 , 99 ]. However, a phase I clinical trial of long-acting somatostatin analogs in OS patients showed that, although long-acting somatostatin analogs can reduce serum IGF-I levels, no clinical response was observed [ 100 ].…”
Section: Different Targets For the Treatment Of Osmentioning
confidence: 99%